Exploring East Asian Undergraduate Students’ Perceptions about the Effectiveness of their Preparation for Study Abroad for Academic Success in U.S. Universities - Chen, Meiren; Bang, Hyeyoung (Journal of International Students, 2020)
We use grounded theory as a framework to explore how preparation for studying abroad affects the academic success of East Asian undergraduate students in U.S. universities. Based on interviews with twelve participants from China, Hong Kong, South Korea, and Taiwan, we found that knowledge of English language and American culture, which is highly involved with their preparation for study abroad and their undergraduate study in the U.S, are two core categories affecting East Asian students’ academic success. High levels of preparation for study abroad help East Asian students better adapt to American universities. At the same time, East Asian students spend more time on English proficiency tests than learning the culture both before and after they arrive to the U.S., which can be detrimental. We suggest that U.S. universities provide more support for cultural adaptation such as learning communities to have active cultural exchanges within context.